Pengaruh Pembelajaran Project Based Learning terhadap Kreativitas Siswa melalui Fotografi Candi Mirigambar Berbasis Blogger MTs Aswaja Tunggangri - Shahrul Nizam; Hendra Pratama (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This research is motivated by the low enthusiasm, participation, and creativity of students in social studies learning which is considered boring and difficult, resulting in low learning outcomes. One effort to overcome this problem is to apply the Project Based Learning (PjBL) learning model based on the Mirigambar Temple photography project through Blogger media. This study aims to determine the effect of PjBL on learning outcomes, creativity, and both simultaneously. The study used a quantitative approach with a quasi experimental nonequivalent control group design. The sample consisted of 20 control class students and 20 experimental class students selected using the purposive sampling technique. The instruments used were creativity questionnaires and learning outcome tests. Data analysis used the Independent Sample T-Test and MANOVA. The results showed that PjBL learning had a significant effect on learning outcomes, creativity, and learning outcomes and creativity of students together. These findings indicate that the application of PjBL through a Blogger-based photography project can create active, enjoyable learning, and is able to optimally increase student potential, so it is worthy of being an alternative strategy for learning social studies in schools.